Pengaruh Kepimpinan Kepala Sekolah Sebagai Supervisor dan Motivasi Kerja Guru terhadap Kinerja Guru di SMA Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun 2024 - Libertin Dewi Resmi Laia; Betty A.S Pakpahan; Liyus Waruwu (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this research is to 1) determine the influence of the principal's leadership as supervisor on teacher performance at SMA Negeri 1 Sipoholon in 2024; 2) Knowing the influence of teacher work motivation on teacher performance at SMA Negeri 1 Sipoholon in 2024; 3) Knowing the influence of the Principal's Leadership as a Supervisor and Teacher Work Motivation Simultaneously on Teacher Performance at SMA Negeri 1 Sipoholon in 2024. With the hypothesis: 1) There is a positive influence of the Principal's Leadership as a Supervisor on Teacher Performance at SMA Negeri 1 Sipoholon in 2024 2 ) There is a positive influence of Teacher Work Motivation on Teacher Performance at SMA Negeri 1 Sipoholon in 2024. 3) There is a positive influence of Principal Leadership as Supervisor and Teacher Work Motivation simultaneously on Performance at SMA Negeri 1 Sipoholon in 2024. The method in this research is a quantitative method with a descriptive statistical approach. The population is all teachers at SMA Negeri 1 Sipoholon, totaling 41 people and this research is a population study. Data were collected using a closed questionnaire with 60 reliable items, with rh>rt α 0.05 for all items and r11:0.90%. The results of data analysis show that there is an influence: 1) Leadership of the Principal as Supervisor at 37.2%, > 0, thus there is a positive influence of Leadership of the Principal as Supervisor on Teacher Performance at SMA Negeri 1 Sipoholon in 2024. 2) Teacher Work Motivation Regarding Teacher Performance, it is 23.8% > 0, thus there is a positive influence of Teacher Work Motivation on Teacher Performance at SMA Negeri 1 Sipoholon in 2024. 3) Leadership of the Principal as Supervisor and Teacher Work Motivation is 41.3% > 0, thus The positive influence of the Principal's Leadership as a Supervisor and Teacher Work Motivation simultaneously on Performance can be found at SMA Negeri 1 Sipoholon in 2024. In conclusion, Ha is accepted and H0 is rejected.